The Role Of BUMDES In the Economic Empowerment Of Village Communities: Peran BUMDES Dalam Pemberdayaan Ekonomi Masyarakat Desa - Idriyanti, Meri; Agustina, Isna Fitria (Indonesian Journal of Public Policy Review, 2023)
This qualitative study investigates the role of Village-Owned Enterprises (BUMDes) in fostering economic empowerment within Ketapang Village, Tanggulangin District, Sidoarjo Regency. Utilizing interviews, observation, and documentation, the research explores the BUMDes' impact on building and developing the economic potential of the local community. Findings suggest that BUMDes play a pivotal role in enhancing the quality of life and societal well-being, strengthening the local economy, and contributing to national economic resilience. However, challenges persist, notably the limited community involvement in decision-making, budgeting, and program evaluation. The study underscores the need for enhanced community engagement to maximize the effectiveness of BUMDes initiatives. Highlight : Role of BUMDes: Examines the pivotal role played by Village-Owned Enterprises (BUMDes) in fostering economic development and empowerment within rural communities. Community Engagement Challenges: Highlights the impediment of limited community participation in decision-making, budgeting, and program evaluation, hindering the success of BUMDes initiatives. Economic Impact: Demonstrates how BUMDes contribute to strengthening the local economy, enhancing the quality of life, and playing a crucial role in the resilience of the national economy Keywords: BUMDes, Economic Empowerment, Community Development, Rural Enterprises, Stakeholder Engagement